PERIPHERAL NERVE SHEATH TUMORS: CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS – A RETROSPECTIVE CASE SERIES OF 46 PATIENTS - Ćurčić, Mihajlo; Radanović, Dražen; Savić, Andrija; Giljača, Sonja; Mrvaljević, Milutin; Misić Mandić, Vanja; Rudić, Marija; Rasulić, Lukas (HEALTH CARE, 2025)
Introduction/Aim: Peripheral nerve sheath tumors (PNSTs) represent a diverse group of neoplasms arising from Schwann cells and fibroblasts of peripheral nerves. Their heterogeneous nature and variable association with neurofibromatosis (NF) syndromes necessitate a comprehensive understanding of their epidemiological and clinical profiles. The aim of this study was to analyze the clinical and epidemiological characteristics of persons with peripheral nerve sheath tumors (PNSTs) diagnosed during the last five years.Methods: In this stusy, the retrospective analysis of 46 patients with histologically confirmed peripheral nerve sheath tumors was conducted. All subjects were included in the study in the period from January 1st, 2020 to January 1st, 2025. All necessary data were collected from the medical records of these patients. Demographic data, tumor type, anatomical location, presence of neurofibromatosis, time from symptom onset to surgery, and clinical manifestations were evaluated.Results: Schwannomas were the most common tumor type (73.9%), followed by malignant peripheral nerve sheath tumors (MPNSTs) (15.2%) and neurofibromas (10.9%). The most frequent tumor localization was the upper extremities. Neurofibromatosis type 1 (NF1) was present in 19.6% of patients. Conclusion: Peripheral nerve sheath tumors are predominantly benign and most commonly located in the upper extremities. Neurofibromatosis remains an important risk factor, particularly in patients with multiple lesions.
Keywords: peripheral nerve sheath tumors, Schwannoma, Neurofibromatosis type 1, MPNST